Boutique HAN’s Handsock / Husna Izzati Sabarudin, Nurin Nadiah Rahim and Nurul Asyiqin Mazihan - Sabarudin, Husna Izzati; Rahim, Nurin Nadiah; Mazihan, Nurul Asyiqin (2025)
HAN's handsock boutique is a partnership business in Bangi, Selangor, speacialize in fashionable Muslimah fashion with particularly HAN's handsock focus on high quality semi waterproof material, non-iron fabric and innovative built-in buttons with various of trending designs and colours. To enhance the accessibility, HAN’s Handsock offers J&T delivery services through our online website, HAN’s handsock provide discounted delivery at the cheapest rate. Our target market includes Muslim women, medical workers, outdoor workers, fashion enthusiasts who appreciate stylish and limited design trendy handsock design. Customer satisfaction is our motivation. We implement a loyalty program for offline customer, offering exclusive card to repeat customer. Furthermore, for online customers, will receive personalized thank-you card with a feedback request via QR code and attractive packaging. This approach allows us to gather the valuable information to make continues improvement in our product quality and design.